2022
DOI: 10.3390/ijms232314724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Expression and Prognostic Value of Genes Encoding Microtubule-Associated Proteins in Lung Cancer

Abstract: Microtubule-associated proteins (MAPs) play essential roles in cancer development. This study aimed to identify transcriptomic biomarkers among MAP genes for the diagnosis and prognosis of lung cancer by analyzing differential gene expressions and correlations with tumor progression. Gene expression data of patients with lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) from the Cancer Genome Atlas (TCGA) database were used to identify differentially expressed MAP genes (DEMGs). Their prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…MAP4 expression is ubiquitous in nonneural samples and plays a key role in microtubule assembly in human cells. Researchers found that the ratio of MAP4 to Stathmin mRNA in NSCLC tissues was higher than that in normal specimens, suggesting that this ratio may be a potential prognostic marker in NSCLC patients (Singharajkomron et al 2022 ). Luo et al studied the relationship between the mRNA transcript level and protein expression level of different MAPs and related prognosis in NSCLC patients (Stanton et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAP4 expression is ubiquitous in nonneural samples and plays a key role in microtubule assembly in human cells. Researchers found that the ratio of MAP4 to Stathmin mRNA in NSCLC tissues was higher than that in normal specimens, suggesting that this ratio may be a potential prognostic marker in NSCLC patients (Singharajkomron et al 2022 ). Luo et al studied the relationship between the mRNA transcript level and protein expression level of different MAPs and related prognosis in NSCLC patients (Stanton et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research mainly focused on a single gene, but little literature described the characteristics of all MAGs. Singharajkomron 17 investigated the prognostic function of microtubule-associated proteins in lung cancer and distinguished six genes as biomarkers. Consistent with this, KIF4A was also identified as a biomarker in this research.…”
Section: Discussionmentioning
confidence: 99%
“…NEK2 (NIMA-related kinase 2) is involved in centrosome duplication, a key process that ensures the correct organization of the MT organizing center of the cell [26]. Accurate cell division is essential for proper sperm development.…”
Section: Microtubule-associated Genes Affect Spermatogenesis By Varia...mentioning
confidence: 99%